The Effect of Giving Boiled Papaya Leaf Water on Blood Glucose Levels in DM Sufferers in the Simpong Community Health Center Working Area - Subchan, Djadid; Nurarifah, Nurarifah; Fajriana, Hasmar; Syafii, Firdaus (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Papaya trees are often found in Indonesia, both fruit, flowers and leaves are commonly used. Papaya leaves are widely used to treat various diseases including diabetes. Indonesia, with 10.7 million diabetes sufferers, is in the top ten countries with the highest number of diabetes cases. Boiled papaya leaves water can be an alternative in controlling blood sugar levels in people with diabetes. The aim of the study was to prove that boiled papaya leaf water is useful for lowering blood sugar levels in diabetes mellitus patients. The materials used were papaya leaves and clean water. The research method, this study is analytical, namely quasi-experimental design using the pre-test method (before treatment) how much blood sugar levels and post-test (after treatment) blood sugar levels were measured after 30 minutes of treatment then compared with the control group. The treatment was in the form of drinking boiled papaya leaf water with a dose of 100 ml from 10 grams of papaya leaves in one gift. The control only drank water. The research results were based on statistical tests, the data distribution was not normal so the Wilcoxon test was carried out. The significance obtained was 0.117 (>0.05) so that H0 was accepted, it mean there was no effect, meaning that boiled papaya leaf water had no effect on reducing blood sugar levels in diabetes sufferers. The conclusion is that boiled papaya leaf water has no effect on lowering blood sugar levels in diabetes sufferers. It is recommended to calculate the dose based on body weight, increase the dose, or grind it first before use.